The Bangladesh Sustainability Compact: an effective exercise of global experimentalist EU governance? - Kenner, Jeff; Peake, Katrina (Cambridge University Press, 2017)
The calamitous Rana Plaza factory collapse in 2013 focused international attention on labour rights’ violations and factory safety in Bangladesh’s dominant ready-made garment industry which is almost wholly dependent on exports to the EU. In response, the EU and the ILO launched the Bangladesh Sustainability Compact, with the core objective of promoting continuous improvement in labour rights and factory safety in the industry. The uniqueness of the Compact stems from its nature as a form of experimentalist governance involving both governmental and non-governmental actors. Being primarily an EU-led initiative based on balancing trade, sustainable development and human rights’ objectives, it is underpinned by the possible option, if the Compact fails, of withdrawing trade preferences. This article will examine the rationale for the Compact, its main features, and its effectiveness as a form of ‘global experimentalist governance’.